Sobre modelagem da decomposição de fitomassa em meio aquático e impactos na qualidade de água de reservatórios - Sousa, Daniel Villela Runkel de (2018)
This thesis presents an investigation on computational modelling of aquatic decomposition of plant organic matter during the filling of fluvial reservoirs and dam’s backwaters. It begins by establishing concepts related to the phenomena, searching for definitions and parameters from the main fields of research, especially regarding time scales. Next, it proposes a water Quality model based on the variable dissolved organic carbon (DOC), besides making a comparison to a validated model, based on the biochemical oxygen demand (BOD), through the simulation of the filling of Tibagi HPP (Paraná state, Brazil). At last, it operates laboratory experiments with samples of the simulated region, in order to determine relevant factors to the usage of filed data on computational Modelling. The results sustain the new conceptual models of multiple decay, leading to a conclude the validity of more integration between areas that study phytomass aquatic decomposition.